Book Reviews. (1st February 2011) - Bush, Christopher; Fraiture, Pierre-Philippe; Frith, Nicki; Gyssels, Kathleen; Keese, Alexander; Looseley, David; Marsh, Kate; Munyankesha, Pascal; Oktapoda, Efstratia; Parris, David L; Parris, David L; Parris, David L; et al.
France/China: Intercultural Imaginings, Alex Hughes (2007) London: Legenda. Research Monographs in French Studies 22. Modern Humanities Research Association and Maney Publishing, 116 pp., ISBN 978-1-904350-93-4 (hbk), 40Postcolonial Eyes: Intercontinental Travel in Francophone African Literature, Aedn N Loingsigh (2009) Liverpool: Liverpool University Press, 216 pp., ISBN 978-1-84631-049-2 (hbk), 65Perspectives Critiques: L'oeuvre d'Hdi Bouraoui, Elizabeth Sabiston and Suzanne Crosta (eds) (2006) Ontario: Srie monographique en sciences humaines/Human Sciences Monograph Series, 415 pp., ISBN 978-0-88667-070-2, paperbackBreton, Andr, Martinique Snake Charmer, with text and illustrations by Andr Masson, translated by David W Seaman, and an Introduction by Franklin Rosemont (2008) Austin, Texas UP, 117 pp., ISBN: 978-0-292-71765-7, hardback, $19.95Native Sons: West African Veterans and France in the Twentieth Century, Gregory Mann (2007) Durham London: Duke University Press, 333 pp., ISBN 0-8223-3768-1 (pbk), $23.95Richesses: Francophone Songwriter Poets, edited and translated by Aidan Hayes (2008) Cork: Southword Editions, 128 pp., ISBN 978-I-905002-30-6 (hbk), 12Incidental Ethnographers: French Catholic Missions on the TonkinYunnan Frontier, 18801930, Studies in Christian Mission, 33, Jean Michaud (2007) Leiden and Boston: Brill, 279 pp., ISBN 978 9004 13996-1 (hbk), 104La langue franaise au Congo-Brazzaville. Manifestation de l'activit langagire des sujets parlants, Mfoutou, Jean-Alexis (2007) Paris: L'Harmattan. 540 pp., ISBN: 978-2-296-03348-1, Hardback, 42REDOUANE Najib (sous la direction), Clandestins dans le texte maghrbin de langue franaise (2008) Paris: L'Harmattan, coll. Autour du texte maghrbin, 258 pp., ISBN 978-2-296-06500-0, 23, 50 la carte: Le roman qubcois (20002005), Gilles Dupuis and Klaus-Dieter Ertler (eds) (2007) Bern, Berlin, Brusses, Frankfurt on Main, New York, Vienna: Peter Lang, 493 pp., ISBN 978-3-631-55340-4, paperback, 49.50/ 37.10Between Languages and Cultures: Colonial and Postcolonial Readings of Gabrielle Roy, Rosemary Chapman (2009) Montreal & Kingston: McGill-Queen's University Press, 308 pp., ISBN 978-0-7735-3496-4 (hbk), 52.25Regards croiss sur le Canada et la France: Voyages et relations du XVIe au XXe sicle, Pierre Guillaume & Laurier Turgeon (eds) (2007) Paris, Qubec: ditions du Comit des travaux historiques et scientifiques, Presses de l'Universit Laval, 396 pp., ISBN 978-2-7355-0629-3/978-2-7637-8577-6, paperback, 30, Cdn$45.Vitalit littraire au Maroc. Autour des textes maghrbins, Najib Redouane (ed.) (2009) Paris: L'Harmattan, 367 pp., ISBN 978-2-296-08214-4 (pbk), 33.50Histoires inventes. La Reprsentation du pass et de l'histoire dans les littratures franaise et francophones, Elisabeth Arend, Dagmar Reichardt and Elke Richter (eds) (2008) Frankfurt: Peter Lang, 269 pp., ISBN 978-3-631-56966-5 (pbk), 29.40Rituals of Memory in Contemporary Arab Women's Writing, Brinda Mehta (2007) Syracuse, NY: Syracuse University Press, 303 pp., ISBN 0-8156-3135-4 (hbk), $45.00